Principals as agents? Investigating accountability in the compensation and performance of school principals - Sherrilyn M. Billger (Institute for the Study of Labor (IZA), 2007)
In this study I examine the relationship between accountability (e.g., state sanctions for poor performance, or the presence of goals required by the district) and public secondary principal pay and school performance. Though such incentives and standards are increasingly common, the existing literature provides little evidence on the effectiveness of these policies. I explore cross-sectional variation in data from the Schools and Staffing Survey, and use quantile regressions where the conditional distributions of pay and school outcomes reflect variation in performance that is not observable in the data. I find that accountability coincides with lower college matriculation rates and lower principal pay, particularly for the best principals. On the other hand, accountability corresponds to higher retention rates at the worst schools. Though they may not be directly rewarded, school principals appear to act as agents for students in danger of dropping out.
urn:nbn:de:101:1-20080415132
Keywords: 330; Allgemeinbildende Schule; Führungskräfte; Leistungsorientierte Vergütung; Kompetenz; Bildungsniveau; Bildungsfinanzierung; USA